Penerapan Metode Edutainment Guna Meningkatkan Kemampuan Mengenal Warna Pada Anak Usia Dini Di TK Al-Hidayah - Mutia Mawardah; Piraini Piraini (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
This article is based on the Community Partnership Program (PKM) which seeks to improve the ability to recognize colors in early childhood. The ability to recognize colors is an aspect of cognitive abilities. Early childhood color recognition can stimulate vision in the brain Color can also induce visual sensitivity. This happens because the color of the object is directly or indirectly exposed to sunlight and visible to the eye. The learning strategy aims to make learning can be achieved well, one of which is the Edutainment strategy that can be used in early childhood learning. The purpose of this study is to improve the ability to recognize colors that will be given to TK-Al Hidayah students and provide an interesting approach method. The method used is observation, interviews and lectures. Based on the results of the application of the edutainment learning method, it can be concluded that the program can provide learning and knowledge to children about basic colors, the edutainment method can make it easier for children to understand the material, the edutainment method can also provide a new learning atmosphere for Al Hidayah Kindergarten children and can be used as recommendations for improving learning methods. It is hoped that this research can provide experience and lessons for the author, especially in education. The author hopes that further practice can develop this research more broadly with different methods.